A temperature adaptive piston design for swash plate type axial piston machines. Issue 1 (2nd January 2017) - Shang, Lizhi; Ivantysynova, Monika
Abstract: The authors propose a temperature adaptive piston design for axial piston machines of swash plate type. The proposed piston helps to keep the film thickness between piston and cylinder close to optimal with respect to energy dissipation while operating temperature can change in a wide range. The authors utilize the thermal deformation of piston and cylinder, which varies with temperature, to design the interface that adapt the gap height to compensate the change of the fluid viscosity with the temperature. An in-house developed fluid-structure and thermal interaction model together with recently developed port and case temperature prediction model are used to analyze the piston/cylinder interface and to predict resulting part temperatures, deformations, the fluid film properties and resulting energy dissipation, friction and leakage of the proposed novel design. The results show a reduction of energy dissipation over a large range of operating temperature for the proposed design compared to the baseline design.